Biocontrol potential of Trichogramma species against Spodoptera frugiperda and their field efficacy in maize. (December 2021) - Jin, Tao; Lin, Yuying; Ma, Guangchang; Liu, Junbin; Hao, Zheng; Han, Shichou; Peng, Zhengqiang
Abstract: We evaluated egg parasitoids of the genus Trichogramma (Hymenoptera: Trichogrammatidae) in the biocontrol of Spodoptera frugiperda (Smith), a recently invaded pest in China. To compare host selection and fitness, the parasitization capacity of seven Trichogramma species were measured with different aged-adults, as well as allowed to parasitize S. frugiperda eggs at different host egg densities in the laboratory. The field trials involved the release of T. chilonis, T. ostriniae, T. confusum, and T. pretiosum, in a maize plantation in Danzhou, Hainan. The results showed that the numbers of eggs parasitized by ten female T. chilonis, T. ostriniae, and T. confusum within the initial 24-h were 101.5, 87, and 93, respectively. The total number of eggs parasitized by T. chilonis, T. ostriniae, T. confusum, and T. pretiosum within the first 96 h were 180, 139, 191.3, and 169, respectively. The most effective egg densities were 35, 30, 40, and 40 eggs/tube (84.8 cm 3 ), with T. chilonis, T. ostriniae, T. confusum, and T. pretiosum affecting 21.7, 18.8, 23.8, and 16, respectively. After T. chilonis, T. ostriniae, T. confusum, and T. pretiosum were released, the parasitism rate on the egg masses ranged from 61.5 % to 87.5 %. The rate that the egg masses did not hatch were 41.7 %, 12.5 %, 15.4 %, and 15.4 %, respectively. Moreover, the rate of plant damage ranged from 36.1 % to 59.7 %. The larvae density on the plants ranged from 0.43 to 0.83 individuals/plant, which was significantly lower than untreated control (95.6 % and 1.37 individuals/plant). Our results are encouraging, the four Trichogramma species are viable biocontrol candidates for S. frugiperda . Highlights: S. frugiperda recently invaded China, in two years it now affects 26 provinces. S. frugiperda can cause signiﬁcant maize yield losses in mainland China. Seven Trichogramma species were assessed as biological control agents. Laboratory and field trials were encouraging in high density pest populations. T. chilonis, T. ostriniae, T. confusum, and T. pretiosum are potential agents.